Impairment of human spatial orientation in the horizontal, but not the vertical plane, due to aging, cognitive decline, or chronic peripheral vestibular loss - Gerb, Johannes; Oertle, Vivien; Onmus, Burak; Dieterich, Marianne; Brandt, Thomas (Frontiers in Aging Neuroscience, 2025)
IntroductionHumans and other vertebrates exhibit anisotropic orientation and navigation skills, with better performances in the horizontal compared to the vertical plane. While horizontal navigation accuracy decreases with higher age, less is known about age effects on vertical spatial abilities. The same is true for disorders which cause spatial memory deficits, e.g., cognitive impairment or chronic peripheral vestibular loss.MethodsIn this study, patients presenting at a tertiary centre for vertigo and balance disorders underwent a bedside test for spatial orientation abilities (3D real-world pointing task, 3D-RWPT), neurological and neuro-otological testing, and a cognitive screening (MoCA). The 3D-RWPT includes a spatial memory paradigm before and after a passive whole-body yaw-axis-rotation, which requires a (cognitively demanding) mental transformation of one’s body position relative to the targets, and the correct integration of vestibular sensory information. To assess the influence of each variable on pointing accuracy, a mixed linear regression model was used.ResultsIn total, 569 patients (302 females; mean age 62.77 ± 14.13 years) were included. In all paradigms of the 3D-RWPT, age constituted a highly significant predictor for angular inaccuracy in the horizontal plane (p < 0.001***), but not in the vertical plane (n.s.). MoCA-scores (patients with cognitive impairment: n = 178) showed significant impact on the horizontal accuracy in the transformation paradigm (p < 0.001***). In the postrotation task, bilateral peripheral vestibular dysfunction (n = 67) was a highly significant predictor for impaired horizontal (p < 0.001***) but not vertical (n.s.) accuracy. Male patients generally outperformed female patients in both planes.DiscussionAging, cognitive decline, or chronic peripheral vestibular loss selectively impair human spatial orientation in the horizontal, but not the vertical plane. A possible explanation is that vertical and horizontal orientation in ground-based species use separate operational modes of spatial memory encoding. The continuous updating of the internal model of the body in space is realized through egocentric representation in the vertical plane and allocentric, that is world-based, representation in the horizontal plane. Additionally, heterogenous ageing patterns of relevant brain structures, and training effects could play a role.